Evaluating the quality of online vs. face-to-face education post-COVID-19: Perspectives from faculty of education members - Alshurai, Saad Alshurai (Journal of Interdisciplinary Studies in Education, 2024)
This study targets the quality of online and face-to-face education in the repercussions of the (Covid-19) pandemic from the point of view of the faculty of Education members at Kuwait University. The descriptive analytical method was adopted. A total of 90 faculty members of Kuwait University were recruited. The results reveal that the quality of education was higher in face-to-face learning in comparison with online learning. However, no statistically significant difference was found between the online and face-to-face evaluation methods according to the perceptions of the faculty members. The study encapsulates recommendations to increase the number of courses to train the faculty members and enhance their skills related to online education, and to redesign the educational curricula and pedagogical strategies to achieve educational outcomes. The findings of the study are helpful to improvise the quality of online learning and teaching and learning experiences of faculty and students of Kuwait University.